Updated checklist and conservation status of Cactaceae in the state of Durango, Mexico - González-Elizondo, Martha; González-Elizondo, M. Socorro; González-Gallegos, Jesús Guadalupe; Tena-Flores, Jorge A.; López Enriquez, I. Lorena; Ruacho-González, Lizeth; Retana-Rentería, F. Isela (Phytotaxa, 2017)
An updated and annotated checklist of Cactaceae in the Mexican state of Durango is provided, supported by a thorough examination of specialized literature and herbarium specimens, as well as field work. Additionally, geographical distribution, endemism and conservation status of the species were analyzed based on a compiled data matrix with 2326 georeferenced records. Cactaceae comprises 137 species and 29 genera in Durango, which represent a high proportion of the Mexican cactus flora: 46−58% at the generic level and 20−23% at the specific level. The estimated richness according to Chao-2 and Jackknife-1 is 143 and 151 species respectively, which means that the inventory we present here for the Cactaceae of Durango is complete in 91 to 96%.  Since no herbarium specimens nor registers in reliable data bases were found to support their presence in the area, 46 taxa were excluded; even so, this inventory increases by 30% the cacti richness previously reported for Durango and provides new information on the distribution range of many species. The richest genera are Mammillaria, Opuntia, Coryphantha and Echinocereus. The highest concentration of species occurs in the arid and semiarid zone of eastern Durango, although there are also some spots with significant richness in the tropical region on the western slopes of the Sierra Madre Occidental. 75% of the species are endemic to Mexico, 41% are regional endemics and 5% are restricted to Durango. New records and relevant novelties are also discussed.